THE WORLD MADE OF SOUND: WHITEHEAD AND PYTHAGOREAN HARMONICS IN THE CONTEXT OF VEDA AND THE SCIENCE OF MANTRA - Amodio, Barbara A (Journal of Dharma, 1992)
The Supreme Devi SarasvatL Mother of the Vedas and of the Worlds, manifests as a totality of name (Nama) and form (Rupa) which literally is the appearing Universe. She is Mother of all possible sounds and plays them on the Vina, the supreme musical instrument. These Sounds are the subtle letters and Ideal Sounds of the Sanskrit alphabet, considered by Veda as divine in origin. The Universe itself is said to emerge from the subtle sounds of the Sanskrit alphabet, a Varnamala or Garland of Letters gross and subtle which functions through the subtle Tattvas (Categories) of creative evolution to exereses into audible sound, light and indeed the entire appearing cosmos. In a profound way, Sarasvati points to Brahman's evolution into the Divine Talk of subtle and Ideal Sound (Sabda Vibration) that constitutes not only words but the created objects (artha) themselves.